2017
DOI: 10.1016/j.nepr.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Student nurses' perceptions of clinical placements in Australian Prison Health Services: A mixed methods study

Abstract: Increasing demands for clinical placements have forced tertiary institutions to look for alternative placements for third year nursing students. While Prison Health Services provide an opportunity for nursing students to engage in care of offender populations with significant chronic illnesses, there has been little evaluation of such placements. Third year undergraduate nurses (18/46) participated in a mixed methods study to provide evidence-based research on students' perceptions of clinical placements in Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Personal safety was students' overriding concern, this finding corresponds with the findings of other studies (Kent-Wilkinson, 2011;van de Mortel et al, 2017). Levels of violence against NHS staff are high; a third have been the subject of violent behaviour within the last year and almost every accident unit nurse reports being the victim of violence (Solheim, 2018).…”
Section: Personal Safetysupporting
confidence: 83%
See 3 more Smart Citations
“…Personal safety was students' overriding concern, this finding corresponds with the findings of other studies (Kent-Wilkinson, 2011;van de Mortel et al, 2017). Levels of violence against NHS staff are high; a third have been the subject of violent behaviour within the last year and almost every accident unit nurse reports being the victim of violence (Solheim, 2018).…”
Section: Personal Safetysupporting
confidence: 83%
“…Practical assessment documents can impede, rather than enhance, individual's development in placements because students strategically collect competencies and skills rather than focussing on the wider learning opportunities on offer (Hunt et al, 2016). Given that other studies have identified a range of transferable nursing skills are available in prisons (van de Mortel et al, 2017) students' concerns were an unexpected finding of this study. However, the reason may be that students had not seen clinics working and so had not witnessed the skills being practiced which, again, emphasises the impact that seeing first-hand had.…”
Section: Achieving Competencies and Skillsmentioning
confidence: 79%
See 2 more Smart Citations
“…However, our study provides an important caveat to the previously reported positive outcomes of other studies in correctional health settings (Applebaum et al 2002;Alemagno et al 2004;Weiskopf 2005;Dhawan et al 2007;Haley et al 2009;Rich et al 2012;Filek et al 2013;Diaz et al 2014;Bouchaud and Swan 2017;Simon et al 2017;van de Mortel et al 2017;Brooker et al 2018;Candamo et al 2018). Our data suggests a more cautionary approach may be required before immersing medical trainees (or their proctors) in correctional healthcare settings.…”
Section: Discussionmentioning
confidence: 51%